Implementation of Islamic Economic Understanding on Individual Behavior - Mohamad Zalfa Islama Alalifi (ICO EDUSHA, 2025)
Understanding Islamic economics plays an important role in shaping individual economic behavior. Islamic economics is not only oriented toward material gain but also emphasizes worship values, ethics, and moral responsibility in every economic activity. Core principles such as justice and honesty in transactions, prohibition of usury (riba), social concern, prudent consumption, and work ethics serve as the foundation for developing ethical economic behavior. Upholding the values of justice and honesty as emphasized in the Qur’an encourages individuals to act with integrity and avoid harming others. The prohibition of riba directs Muslims toward lawful business activities, while the teaching of generosity promotes social solidarity and reduces economic inequality. Additionally, the principle of avoiding excessive consumption fosters a simple and frugal lifestyle. The Islamic work ethic affirms that working is part of worship, thus requiring professionalism and responsibility. By applying these principles, Muslim individuals can develop balanced economic behavior that aligns worldly interests with the hereafter, thereby creating an economic life that is just, moral, and beneficial for the wider community.